1987
DOI: 10.1148/radiology.162.3.3809497
|View full text |Cite
|
Sign up to set email alerts
|

Pseudarthrosis following lumbar fusion: detection by direct coronal CT scanning.

Abstract: Twenty patients with fusions of the lumbar spine (seven with pseudarthrosis, 11 with solid bony fusions, and two with fusions that appeared solid but assessment was complicated by the presence of surgical hardware) underwent computed tomographic (CT) scanning in the supine position in the axial plane and, employing a specially designed seat, in the coronal plane. Three-millimeter contiguous sections were acquired. The direct coronal images were compared with those reformated from the axial images. The higher-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

1993
1993
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(17 citation statements)
references
References 0 publications
0
16
0
Order By: Relevance
“…Until now, most studies focus on morphological imaging techniques to evaluate the healing process of intercorporal fusions. Obviously, there seems to be no uniform radiological criteria for assessing intercorporal fusion by plain radiographs or CT [10,[15][16][17][18]. 18F-fluoride PET/(CT) on the contrary has mostly been used in the assessment of malignant bone abnormalities [19][20][21][22][23].…”
Section: Discussionmentioning
confidence: 99%
“…Until now, most studies focus on morphological imaging techniques to evaluate the healing process of intercorporal fusions. Obviously, there seems to be no uniform radiological criteria for assessing intercorporal fusion by plain radiographs or CT [10,[15][16][17][18]. 18F-fluoride PET/(CT) on the contrary has mostly been used in the assessment of malignant bone abnormalities [19][20][21][22][23].…”
Section: Discussionmentioning
confidence: 99%
“…18 Similarly, Chafetz et al demonstrated that direct coronal CT scanning may be more sensitive than 2D reconstructed coronal CT images for the detection of pseudarthrosis. 8 Zinreich and colleagues reported that 3D CT reconstruction may be more sensitive than 2D CT reconstruction for the detection of pseudarthrosis. 26 Siambanes and Mather demonstrated that multiplanar CT imaging detected pseudarthrosis in patients who had undergone PLIF, compared with plain radiography, which had suggested a solid fusion.…”
Section: Computed Tomographymentioning
confidence: 99%
“…More recently, thin-section helical CT scanning has become the most reliable method for assessing fusion [4,13]. Reformatted coronal and sagittal CT images make it possible to more clearly evaluate osseous continuity within the graft segment.…”
Section: Discussionmentioning
confidence: 99%
“…CT has developed into the preferred method for assessing interbody fusion [4,13]. It is rapid and provides reformatted images in the coronal and sagittal planes.…”
Section: Introductionmentioning
confidence: 99%